Effect of mean stress in very high cycle fretting fatigue of a bearing steel. (August 2021) - Teng, Zhenjie; Wu, Haoran; Huang, Zhiyong; Starke, Peter
Highlights: Very high cycle fretting fatigue tests with mean stress were successfully performed by ultrasonic fatigue system. Fretting reduced the material's fatigue strength when compared to plain fatigue, and further reduced by the effect of mean stress. The main damage in fretting fatigue was delamination with typical damage pattern in debris pits. The tiny particle debris produced by adhesion can alleviate the crack propagation in fretting fatigue. Abstract: Very high cycle fretting fatigue tests of high carbon chromium GCr15 steel were carried out using an ultrasonic fatigue system to investigate the fatigue strength and the mechanism of its wear and fracture in the damaged area. Fretting reduced the fatigue strength in contrast to the case of plain fatigue, which could escalate even further with the existence of mean stress. Some models were proposed based on the morphologies characterized by a scanning electron microscope: (i) four specific regions on the fracture surface were defined according to the evolution of cracks; (ii) formation of fretting fatigue cracks was analyzed; and (iii) how fretting and mean stress affected the crack propagation after the formation of cracks was analyzed.